Paracoccidioidomicose de localização genital externa: Relato de seis novos casos e revisão da literatura - Marques, Silvio Alencar [UNESP]; Tangoda, Lilian Kanawa; de Camargo, Rosangela Maria Pires [UNESP]; Stolf, Hamilton Ometto [UNESP]; Marques, Mariangela Esther Alencar [UNESP] (FapUNIFESP (SciELO), 2012)
Background: Paracoccidioidomycosis is a systemic mycosis of dermatological interest due to the frequency of cutaneous and mucosal lesions. The involvement of the external genitalia is extremely rare and few cases have been reported. Objective: To study the prevalence of external genitalia lesions in paracoccidioidomycosis patients, identify clinical characteristics and compare with what is observed in the specific literature. Methods: This is a cross-sectional, descriptive study, with focus on paracoccidioiodomycosis patients with external genitalia lesions. The demographic and clinical aspects of cases were compared with what has been reported so far on LILACS, SciELO e MEDLINE data bases. Results: Data of 483 cases of paracoccidioidomycosis were studied in a 42-year period. Six (1.2%) patients showed specific lesions on external genitalia. Five patients were male with mean age of 47.2 years and all of them presented with the chronic multifocal clinical form. Only one, a 15-year-old female patient was observed who showed a subacute clinical form, juvenile type. Conclusions: Compromise of the genitourinary tract among paracoccidioidomycosis patients is rare and even rarer when only the external genitalia are considered. As observed in the classical picture of paracoccidioidomycosis patients, the male gender and the chronic multifocal clinical form prevailed in the present study. © 2012 by Anais Brasileiros de Dermatologia.
Paracoccidioidomycosis of external genitalia: Report of six new cases and review of the literature
Keywords: Dermatology; Genitalia; Mucous membrane; Paracoccidioidomycosis